Reusable superparamagnetic nanocomposite particles for magnetic separation of iron hydroxide precipitates to remove and recover heavy metal ions from aqueous solutions - Mandel, Karl; Hutter, F.; Gellermann, C.; Sextl, G. (Separation and Purification Technology, 2013)
Superparamagnetic nanocomposite microparticles act as seeds for iron hydroxide precipitates. Flocculation of iron hydroxide is applied to adsorb and entrap heavy metal ions dissolved in water. The flocculation product gets deposited on the surface of the nanocomposite microparticles. Due to the nano-property superparamagnetism the particles are switchable magnets and can be separated together with their load from water by an external magnetic field gradient. In an acidic solution, particles are cleaned by dissolution of the iron hydroxide precipitate. A silica surface protects the superparamagnetic microparticles from dissolution rendering their reuse as seeds and magnetic carriers possible. Repetition of the separation and recovery process leads to a significant increase of concentration of heavy metals in the acid cleaning solution, which paves the way for further recycling procedures of these elements. © 2013 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Heavy metal removal; Magnetic seeding; Magnetic separation; Recycling; Superparamagnetic particles; Water purification